Characterization of Plant Pathogenic Bacteria Causing Crown Rot Disease in Papaya (Carica papaya L.) - Rania, Khansa Diva; Aini, Luqman Qurata (University of Brawijaya, 2025)
Papaya (Carica papaya L.) is an annual plant belonging to the Caricaceae family. Papaya populations in Indonesia can be found in almost all regions. The extensive papaya cultivation areas in Indonesia often involve planting on wild land, which exposes papaya plants to various diseases. Crown rot disease is an example of a disease in papaya. Papaya plantations in Jajag, Gambiran, Banyuwangi Regency, are known to be affected by stem rot. To determine the appropriate disease control measures, it is necessary to identify the cause of the wet rot disease in papaya plant stems. The research was conducted through several stages, including sampling, media preparation, isolation of pathogenic bacteria, hypersensitivity tests, pathogenicity tests, potato soft rot tests, colony and cell morphological observation, Gram staining, oxidative/fermentative, yellow colony on YDC media, lecithinase, catalase, sensitivity to erythromycin, carbohydrate fermentation, and temperature treatment at 37°C and 40°C. The results showed that the plant pathogenic bacteria causing crown rot at the base of the stem in papaya plants were isolates B1 and B2, belonging to the group of Pantoea sp.; isolates B3, B6, and B7, belonging to the group of Erwinia sp.; and isolates B4 and B5, belonging to the group of Dickeya sp..